'They Should See Us as a Symbol of Reconciliation': Youth Born of Genocidal Rape in Rwanda and the Implications for Transitional Justice. (28th April 2019) - Denov, Myriam; Kahn, Sara
Abstract: Rape and other brutal forms of sexual violence are now widely acknowledged as weapons of war, designed not only to violate and terrorize individual victims but also to denigrate the larger communities to which victims belong. Yet children born of conflict-related sexual violence remain largely overlooked as victims to the profound consequences of sexual violence and excluded from transitional justice processes aiming to reconcile and repair post-conflict societies. Through in-depth qualitative interviews and focus groups with 60 participants born of genocidal rape in Rwanda, this study sought to examine the experiences and lived realities of this specific group of conflict-affected young people. The voices and perspectives of Rwandan youth born of genocidal rape draw attention to the complex reality of victimhood, social stigma and identity as a result of conflict-related sexual violence, alongside participants' desire for societal recognition. Our findings suggest that the inclusion of this population of youth is urgently needed as part of the broader initiatives addressing conflict-related sexual violence and transitional justice in the aftermath of war and genocide.